Digitalization in the Service Sector - Ishonkulova Feruza Asatovna; Khamitov Mansurkhon Jamshedovich (International Journal on Orange Technologies, 2022)
The subject of the study is the development of the service sector in the framework of the digitalization of the economic space. The goal is to clarify the processes of dependence of the development of the service sector in the context of the digital transformation of the economy at the present stage of development of the national economy. The author sets the following tasks: to analyze the main economic indicators of the development of the service sector; identify the features of digital transformation of business in this area; determine the patterns of development of the service sector under the influence of digital processes. As a result, the author reveals patterns and trends in the development of the service sector under the influence of digital processes - an increase in the activity coefficient and a decrease in the number of personnel. The obtained materials can be used to promote the development of the service sector at the macro and micro levels, which determines the value of this study. Scientific novelty lies in the formed matrix of the relationship between the development of individual service industries and business digitalization processes. The article reveals the heterogeneity in the field of digitalization of business processes in the service sector, as well as the trend towards a relative increase in the efficiency of enterprises in industries characterized by high digital activity.